Pemahaman Akseptor Tentang Baby Booming dan Tingkat Pengetahuan Tentang Program KB pada Masa Pandemi Covid-19: Acceptors' Understanding of Baby Booming and Level of Knowledge of Family Planning Programs During the Covid-19 Pandemic - Widyawati, Sigit Ambar; Kustiyono; Sofiyanti, Ida; Najib (Universitas Ngudi waluyo, 2024)
Baby boom or soaring pregnancy rates including unwanted pregnancies (KTD). This is related to the Corona Virus Disease-19 (Covid-19) pandemic which has caused a decrease in the number of family planning (KB) services nationally. Family Planning according to the World Health Organization (WHO) is an action that helps individuals or married couples to avoid unwanted births, get the desired birth, regulate birth intervals, control the time of birth in relation to the age of the husband and wife, determine the number of children in the family. Long-term family planning services are an effective method of preventing pregnancy, but direct contact is required which is disrupted due to physical distancing efforts. To determine the acceptor's understanding of the baby boom and the level of knowledge about the KB program during the Covid-19 Pandemic. This research method uses a survey technique with a questionnaire given to selected acceptors in Semarang Regency. The number of respondents was 50 people. Results: It was found that 35 respondents (70%) had good knowledge about the definition of baby booming, efforts to prevent baby booming (74%), good knowledge of NKKBS (78%), and a good level of knowledge about the KB program (76%). Abstrak Baby booming atau angka kehamilan yang melonjak termasuk terjadinya kehamilan tidak diinginkan (KTD). Hal ini berkaitan dengan adanya pandemi Corona Virus Disease-19 (Covid-19) yang menyebabkan penurunan jumlah pelayanan keluarga berencana (KB) secara nasional. Keluarga Berencana menurut World Health Organisation (WHO) adalah tindakan yang membantu individu atau pasangan suami istri untuk menghindari kelahiran yang tidak diinginkan, mendapatkan kelahiran yang diinginkan, mengatur interval kelahiran, mengontrol waktu saat kelahiran dalam hubungan dengan umur suami dan istri, menentukan jumlah anak dalam keluarga. Pelayanan KB jangka panjang merupakan metode efektif pencegahan kehamilan, namun diperlukan adanya kontak langsung yang terganggu karena adanya upaya physical distancing. Mengetahui pemahaman akseptor tentang baby booming dan tingkat pengetahuan tentang program KB Pada Masa Pandemi Covid-19. Metode penelitian ini menggunakan teknik survei dengan kuesioner yang diberikan kepada akseptor terpilih di Kabupaten Semarang. Jumlah responden sebanyak 50 orang. Didapatkan sebanyak 35 responden (70%) memiliki pengetahuan baik tentang pengertian baby booming, upaya pencegahan baby booming (74%), pengetahuan yang baik NKKBS (78%), dan tingkat pengetahuan yang baik tentang program KB (76%).